Low Knowledge and Unawareness of the Health Promotion as the Determinant Factors in Non-Compliance to the Mass Drug Administration Program - Annashr, Nissa Noor; Amalia, Icca Stella; Dinh, Hoa Thi Phuong (UI Scholars Hub, 2021)
From the total population of the community in Kuningan District, 78.61% were taking filariasis drugs in the Mass Drug Administration (MDA) program in 2017. Cilimus Subdistrict became a filariasis-endemic area in Kuningan with 72.39% of the MDA program coverage in 2017 (government target >86%). The purpose of this study was to analyze the determinant factors of compliance with the MDA program. The study was an analytical study with a cross-sectional design and conducted from May to June 2018. The sample of 106 people was taken from the population living in Cilimus Subdistrict, Kuningan District, using a simple random sampling technique. Independent variables were collected by a constructed questionnaire included age, education level, knowledge, attitude, health promotion, and family support. A questionnaire also measured compliance with MDA as a dependent variable. Data analysis consisted of univariate, bivariate (chi-square and Fisher exact test), and multivariate analyses (multiple logistic regression). The results showed that the variables of knowledge, attitude, MDA health promotion, and family support influence compliance with the MDA (p-value < 0.05). Low knowledge and unawareness of the MDA health promotion proved to be the dominant factors in non-compliance with the MDA program.